IMPLEMENTASI PARIS AGREEMENT TERHADAP KEBIJAKAN KEHUTANAN INDONESIA - Utami, Tri Wahyu; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study describe about implementatioan Paris Agreement in indonesia’s forest policy. Paris Agreement which agreed by Indonesia and others country gave new dream for world future after increased the climate change in the world. In This script will look at issue and problems with International Relation paradigm thought of study, analize, theory and perspective.This reasech use conceptual base with green political concept, and implementation of paris agreement be a focus discussion. This research have national state level, constructivis perspective and green theory of methodology qualitative research.The implementation that have done by Paris Agreement are agremment of Indonesia legislative assembly have made the constitution of Republic Indonesia (Nomor 16 Tahun 2016) about validation of paris Agreement To The United Nations Framework Convention On Climate Change. That constitution valided in Jakarta, at October 24th 2016 by President Of Republic Indonesia, Joko Widodo and valided by ministry of law and human right, Yasonna H. Laoly.Keywords: Implementation, Paris Agreement, Policy